A NOTE ON TACHERS’ ROLES IN THE APPLICATION OF CARD GAMES IN FOREIGN LANGUAGE TEACHING AND LEARNING - Daiho Kitaoka (XALQARO ILMIY-AMALIY ANJUMAN "TA’LIM MAYDONI TENDENSIYALARI: KOMPETENTSIYALAR, INNOVATSIYALAR VA TEXNOLOGIYALAR", 2025)
This paper is a preliminary report for the result of practice sessions for Japanese oral skills through playing card games. In the present study, extracurricular practice sessions were organized to offer university students in China with opportunities to practice Japanese, which they studied for their minor, while engaging in card games in a comfortable and friendly setting. This paper provides some notes and caveats when implementing game-based lessons, based on the experiences and reflections of the sessions, reserving for future research the analysis of students’ performances and the practical and theoretical implications for foreign language pedagogy. In particular, this paper focuses on the roles of teachers in game-based classrooms.